BENTUK KIGO PADA HAIKU DAN ISI SINDIRAN PADA SENRYU OLEH MAHASISWA SASTRA JEPANG UNIVERSITAS BRAWIJAYA - Fitriana Puspita Dewi; Elizabeth Worobroto; Santi Andayani (Universitas Diponegoro, 2016)
In the Japanese literature, poetry has its own type and form, including Haiku and Senryu with 5-7-5 syllabic structure. Another prominent characteristic of Haiku is the topic concerning beauty of nature and the elements like Kigo or Kisetsu no Kotoba (the words marking the seasons) in which it shows the closeness of Japanese people with nature. Senryu has humorous and witty elements, including satire and the story about people; it does not describe season at all. Therefore, cultural background and social condition of society will affect content and form of the satire. This research aims to analyze the form of kigo in haiku and the content of satire in senryu, written by students of Japanese Literature in Brawijaya University. This research used qualitative descriptive methodology. The research shows the result that kigo ame and kigo taiyou are the most frequently used forms. In senryu, the contents of satire are love, student life, and physical depiction.